Frequency of Thrombocytopenia in Plasmodium VIVAX Malaria Among Children - Hashmat Ullah Khan, Sadia Jehanzeb, Bushra Mehreen, Rabbia Shaheen, Saif Ur Rehman, Muhammad Furqan Ullah Babar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of the study was to quantify the incidence of thrombocytopenia in paediatric plasmodium vivax malaria. Methods: After the approval from institution review board, this cross-sectional study was conducted at Department of Paediatrics, Hayatabad Medical Complex, Peshawar, from 5 October 2018 to 5 April 2019. A total of 172 children’s were recruited in this research. At first, those who had a sudden start of a fever without any other symptoms were chosen. It was determined that the patient had hepatosplenomegaly and was treated accordingly. Blood tests, such as thick and thin smear microscopy, were performed on people who were thought to have malaria. Patients who met the study’s inclusion and exclusion criteria were considered for participation. The peripheral smear was used to test for thrombocytopenia in patients with vivax malaria. Results: Mean ± S. D of age of the study participants was 7±7.85years. Among the study participants, 65% were male and 35% were females. Mean ± S. D of fever duration of the study participants was 4 ± 2.73 days, with 33 % have fever duration less than and equal to 4 days, while 67% of the study participants have more than 4 days. In 5% of study participants previous history of malaria and malaria vivax was observed, and 3% of the study participants have suffered from congenital malaria. Mean ± S. D of gestational age of the study participants was 37 ±3.21 weeks. Among the 172 recruited participants 68% had thrombocytopenia. Conclusion: Our study concludes that the frequency of thrombocytopenia was 68% in children presenting with in plasmodium vivax malaria. Keywords: thrombocytopenia, plasmodium, vivax malaria, children